Some necessary considerations about the postoperative intraabdominal infection - Iliana Guerra Macías; Juliet Suárez Guerra; Jaila Suárez Guerra (Revista Cubana de Medicina Militar)
Postoperative intra-abdominal infection is a global health problem and requires multidisciplinary care to correct it. Its complexity lies in the early diagnosis and relaparotomy to control it. It is a complication of abdominal surgery, whose comprehensive clinical surgical care is the responsibility of general surgeons, pediatric surgeons, obstetricians, proctologists, urologists, imaging specialists, anesthesiologists, and intensivists. Therefore, the mastery of essential aspects is necessary on the treating doctors, as part of the permanent and continuous professional improvement that allows them to guarantee the necessary quality of care of the affected, as the only way to reduce the high rates of morbidity and mortality due to this dreaded condition.